(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the role of games in teaching English to primary school learners, highlighting their effectiveness as a modern instructional tool. It emphasizes that traditional teaching methods may not fully engage young learners, who often require interactive and stimulating activities to maintain focus and interest. Games, in this context, serve as a dynamic medium that combines learning with play, making the acquisition of language skills more natural and enjoyable. The paper discusses the cognitive, emotional, and social benefits of using games in the classroom, including enhanced motivation, better memory retention, and increased participation. It also categorizes different types of educational games suitable for primary school students and offers practical guidance for teachers on how to implement them effectively. Ultimately, the article advocates for a balanced approach to language instruction where games are not merely used for entertainment but as structured, purposeful tools that support meaningful language learning outcomes.